Development growth of beach resorts: practitioners' perspective - Awang, Khairil Wahidin; Mustapha, Mazlina (Inderscience Publishers, 2021)
The increase in demand for natural touristic features such as sandy beaches, colourful corals and warm weather at island destinations has led to the mushrooming of beach resorts. Beach resorts equip island destinations with places to stay for tourists while letting them enjoy islands' touristic features. Beach resorts accommodate both international and domestic tourists at an ever increasing trend. Nevertheless, the construction and development of these resorts at large was on an ad hoc basis. Although the existence of this segment of the accommodation sector is significant to the growth of the tourism industry, its unregulated development has led to many physical and socio-culture drawbacks. This paper aims to explore this process of development, filling the gaps in tourism destination planning. In-depth interview and observation formed the primary mode of collecting data, underpinning the qualitative approach adopted in this study. Findings suggest that increased number of tourists, international and domestic, fuelled spurious development of beach resorts. Demand for accommodation space spiked during weekends, long weekends and public holidays. Development was rapid and uncontrolled, although there were evidence that the government had plans to regulate this process.